THE FIRST DISCOVERY OF APARTIDAE (AMMONOIDEA) IN THE CARNIAN OF NORTHEASTERN ASIA - Konstantinov A.G. (My University, 2006)
A new genus Siberioklipsteinia (with the type species S. dagysi sp. nov.) and a new species Arctoarpadites nelgesensis are described from the Carnian of the Kharaulakh Range and Yana Upland (eastern Yakutia). The new data allow refinement of the taxonomy of Carnian ammonoids of northeastern Asia and emendation of some details of their geographical differentiation. The new ammonoid taxa belong to the family Arpaditidae, which was not previously recorded from the eastern Boreal Realm. © Pleiades Publishing, Inc. 2006.
Keywords: AMMONOIDEA; ARPADITIDAE; CARNIAN; NORTHEASTERN ASIA; Mesozoic::Triassic::Upper::Carnian; Мезозой::Триасовая::Верхний::Карнийский